Pengelolaan Keuangan dan Digital Marketing untuk Usaha Ecoprint Rumah Tangga Berbasis Kewirausahaan - Susilowati, Retno Yuni Nur; Alvia, Liza; Desriani, Neny; Fathia, Syaharani Noer; Majidah, Rona (Penerbit Goodwood, 2024)
Purpose: This community service aims to develop ecoprint creative fabric-making skills that involve the dyeing process with natural dyes and to improve understanding of financial management in a simple business for homemakers so that housewives can contribute to earning additional income. Methodology: The activities carried out in this service activity are: socialization program, socialization is carried out by downloading representatives of housewives by explaining the objectives of the activity and plans for service activities. Training making ecoprints, this activity m conduct ecoprint skills training and accompany trainees to practice ecoprint techniques. To make ecoprints can be done through scouring on new fabrics, mordanting fabrics, proses ecoprint and fixation process. Results/findings: As a result of the service, participants could make tablecloths and hijabs with the application of ecoprint skills. Participants were able to manage simple business finances. In contrast, service participants were motivated to start entrepreneurship and calculate the cost of goods sold to help improve the family economy. Conclusion: Participants can make artisans' ecoprint fabrics by bringing up a new image of their designs and branding as environmentally friendly Muslim fashion craftsmen; participants can also calculate the cost of goods sold to sell prices with profits to improve the family economy.